2018
DOI: 10.1186/s12879-018-3169-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and associated factors of patients with extensive drug-resistant tuberculosis: an emerging public health crisis in China

Abstract: BackgroundLimited treatment options of extensive drug-resistant tuberculosis (XDR-TB) have led to its high mortality worldwide. Relevant data about mortality of XDR-TB patients in literature are limited and likely underestimate the real situation in China, since the majority of patients with XDR-TB are lost to follow-up after discharge from TB hospitals. In this study, we sought to investigate the mortality and associated risk factors of Human Immunodeficiency Virus (HIV)-negative patients with XDR-TB in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Patients with lower BMI (<18.5 kg/m 2 ) had 2.45 the risk to develop poor treatment outcomes. Studies that were done by Dheda et al (2012), Kurbatova et al (2012), Leimane et al (2005), Nair et al (2017), andBei et al (2018) also supported this. The other risk factor was anemia; patients with any type of anemia had 2.33 times the risk to have a poor treatment outcome compared to their counterparts.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Patients with lower BMI (<18.5 kg/m 2 ) had 2.45 the risk to develop poor treatment outcomes. Studies that were done by Dheda et al (2012), Kurbatova et al (2012), Leimane et al (2005), Nair et al (2017), andBei et al (2018) also supported this. The other risk factor was anemia; patients with any type of anemia had 2.33 times the risk to have a poor treatment outcome compared to their counterparts.…”
Section: Discussionsupporting
confidence: 54%
“…The pooled incidence density rate of mortality in this study was 9.28/1000 PMs. Likewise, Balbanova et al (Balabanova et al, 2011) from Eastern Europe, Ali et al (2019) from Sudan and Bei et al (2018) from China reported 9.12/1000PMs, 10.44/1000 PMs, and 10.67/1000 PMs respectively. The case of China was among XDR-TB patients.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to information recently published by the World Health Organization (WHO), the 20 countries with the highest TB burden based on the absolute number of incident cases and 10 countries with the highest TB burden based on the severity of the disease are all developing countries [5]. As a developing country with a high TB burden, China is currently facing a serious health problem due to the prevalence of tuberculosis [5,6]. Despite a decrease in smear-positive TB cases, from 170 to 59 cases per 100,000 individuals during 1990-2010, TB has always ranked among the top five on the national list of notifiable infectious diseases in China [7].…”
Section: Introductionmentioning
confidence: 99%